Regulation of Plant Immunity by Nuclear Membrane-Associated Mechanisms - Fang, Yiling; Gu, Yangnan (Frontiers in Immunology, 2021)
Unlike animals, plants do not have specialized immune cells and lack an adaptive immune system. Instead, plant cells rely on their unique innate immune system to defend against pathogens and coordinate beneficial interactions with commensal and symbiotic microbes. One of the major convergent points for plant immune signaling is the nucleus, where transcriptome reprogramming is initiated to orchestrate defense responses. Mechanisms that regulate selective transport of nuclear signaling cargo and chromatin activity at the nuclear boundary play a pivotal role in immune activation. This review summarizes the current knowledge of how nuclear membrane-associated core protein and protein complexes, including the nuclear pore complex, nuclear transport receptors, and the nucleoskeleton participate in plant innate immune activation and pathogen resistance. We also discuss the role of their functional counterparts in regulating innate immunity in animals and highlight potential common mechanisms that contribute to nuclear membrane-centered immune regulation in higher eukaryotes.